2006
DOI: 10.1177/0040517506062262
|View full text |Cite
|
Sign up to set email alerts
|

Regressional Estimation of Ring Cotton Yarn Properties from HVI Fiber Properties

Abstract: The physical characteristics of a fiber determine its processing behavior, production efficiency and finally yarn and fabric quality. Therefore, predicting the quality characteristics of yarns, such as the tensile properties from the raw material properties, was the main purpose of many studies in the last century. In addition to raw material processing conditions, preparation stages, machine parameters and the spinning method also have considerable effects on the yarn properties. Generally two approaches were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 16 publications
(28 reference statements)
6
45
0
Order By: Relevance
“…Testing with a High Volume Instrument (HVI) (Uster Technologies AG, Uster, Switzerland) (Schleth et al 2007) is standard practice to determine these fibre attributes in many production regions, and these properties are used to establish the value of cotton fibre (USDA 2005). HVI properties explain much but not all of the variation in yarn strength, and significant work has been conducted into understanding the relative contribution of fibre properties (El Sourady et al 1974;Ureyen and Kadoglu 2006) and how these properties relate to yarn performance, through the development of fibre quality indices (Hunter 2004) or modelling techniques (Ramey et al 1977;Zurek et al 1987;Cheng and Adams 1995). There remain opportunities to include fibre quality measurements that may better explain yarn strength, for example by employing alternative attributes for, among others, the still commonly used micronaire measure.…”
Section: Introductionmentioning
confidence: 99%
“…Testing with a High Volume Instrument (HVI) (Uster Technologies AG, Uster, Switzerland) (Schleth et al 2007) is standard practice to determine these fibre attributes in many production regions, and these properties are used to establish the value of cotton fibre (USDA 2005). HVI properties explain much but not all of the variation in yarn strength, and significant work has been conducted into understanding the relative contribution of fibre properties (El Sourady et al 1974;Ureyen and Kadoglu 2006) and how these properties relate to yarn performance, through the development of fibre quality indices (Hunter 2004) or modelling techniques (Ramey et al 1977;Zurek et al 1987;Cheng and Adams 1995). There remain opportunities to include fibre quality measurements that may better explain yarn strength, for example by employing alternative attributes for, among others, the still commonly used micronaire measure.…”
Section: Introductionmentioning
confidence: 99%
“…Generally two approaches were used in studies to predict yarn quality from fiber and yarn characteristics: theoretical approaches and statistical approaches. Statistical or empirical models have relatively higher predictive power than theoretical models [1][2][3][4]. Multiple regression analyses are the most common statistical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple regression analyses are the most common statistical methods. Several regression equations have been established [1][2][3][4][5]. Prediction of cotton yarn properties from fiber properties have also been reviewed in details [6].…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis demonstrated that there was a nearly linear relationship between fi bre properties measured with HVI and sirospun yarn properties. Because of this, the linear multiple regression analysis method was chosen for this study [10].…”
Section: Resultsmentioning
confidence: 99%